Hubungan Status Hipertensi dan Kadar Hemoglobin dengan Kejadian Prematur pada Ibu Melahirkan di Royal Maternity General Hospital Tahun 2024 - Budiani, Novi; Hanum, Parida; Rosmawati Purba, Grace; Fitriana, Fitriana; Fitriani, Fitriani; Yanti Nasution, Nofri (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2025)
The main causes of neonatal mortality are LBW including prematurity, asphyxia and infection. The cause of preterm birth is largely unknown. One of the causes of prematurity is insufficient nutrition (anemia) and hypertension due to pregnancy. The purpose of this study was to determine the relationship between hypertension status and hemoglobin levels with the incidence of prematurity in mothers giving birth. The type of research used is quantitative using an analytic observational design research design with a retrospective approach. The population in this study were all mothers who gave birth at the Royal Maternity General Hospital which amounted to 285 people. The technique of taking subjects using simple random sampling as many as 74 people. The instruments used in this study were observation sheets to assess hypertension (blood pressure), and the value of hemoglobin (Hb) levels. The research data analysis was univariate and bivariate analysis with chi square test. The results explained that there was a relationship between hypertension status (p=0.002) and hemoglobin levels (p=0.000) with the incidence of preterm labor in mothers. The conclusion of this study is that there is a relationship between hypertension status and hemoglobin levels with the incidence of preterm labor in mothers.